The relationship between insulin and glucagon concentrations in non‐diabetic humans. Issue 13 (13th July 2022) - Laurenti, Marcello C.; Arora, Praveer; Dalla Man, Chiara; Andrews, James C.; Rizza, Robert A.; Matveyenko, Aleksey; Bailey, Kent R.; Cobelli, Claudio; Vella, Adrian
Abstract: Abnormal postprandial suppression of glucagon in Type 2 diabetes (T2DM) has been attributed to impaired insulin secretion. Prior work suggests that insulin and glucagon show an inverse coordinated relationship. However, dysregulation of α‐cell function in prediabetes occurs early and independently of changes in β‐cells, which suggests insulin having a less significant role on glucagon control. We therefore, sought to examine whether hepatic vein hormone concentrations provide evidence to further support the modulation of glucagon secretion by insulin. As part of a series of experiments to measure the effect of diabetes‐associated genetic variation in TCF7L2 on islet cell function, hepatic vein insulin and glucagon concentrations were measured at 2‐minute intervals during fasting and a hyperglycemic clamp. The experiment was performed on 29 nondiabetic subjects (age = 46 ± 2 years, BMI 28 ± 1 Kg/m 2 ) and enabled post‐hoc analysis, using Cross‐Correlation and Cross‐Approximate Entropy (Cross‐ApEn) to evaluate the interaction of insulin and glucose. Mean insulin concentrations rose from fasting (33 ± 4 vs. 146 ± 12 pmol/L, p  < 0.01) while glucagon was suppressed (96 ± 8 vs. 62 ± 5 ng/L, p  < 0.01) during the clamp. Cross‐ApEn was used to measure pattern reproducibility in the two hormones using glucagon as control mechanism (0.78 ± 0.03 vs. 0.76 ± 0.03, fasting vs. hyperglycemia) and using insulin as a control mechanism (0.78 ± 0.02 vs. 0.76 ± 0.03, fasting vs. hyperglycemia). Values did not differ between the two scenarios. Cross‐correlation analysis demonstrated a small in‐phase coordination between insulin and glucagon concentrations during fasting, which inverted during hyperglycemia. This data suggests that the interaction between the two hormones is not driven by either. On a minute‐to‐minute basis, direct control and secretion of glucagon is not mediated (or restrained) by insulin. Abstract : This manuscript suggests that insulin pulses do not necessarily regulate glucagon secretion in humans.